Convenience, food and family lives. A socio-typological study of household food expenditures in 21st-century Belgium. (1st November 2015) - Daniels, Sarah; Glorieux, Ignace
Highlights: Household demand for convenience is measured using food expenditure budget shares. 30 percent of households' food budgets is spent on (semi-) convenience foods. Convenience foods do not enjoy similar success across different household segments. Semi-prepared foods are closer to the conventional definition of cooking. Abstract: This article aims to uncover the extent to which convenience foods have become embedded in today's diets. The paper focuses on households' food expenditures, collected by Statistics Belgium in 2005. The results show that households' reliance on (semi-) convenience food items and away-from-home consumption clearly differs over the life-course and amongst different social groups. Findings show that single-living households (single men in particular) look for more convenience in their food preparation patterns compared to couples and households with children. The consumption of semi-convenient meal components seems to be more closely related to the conventional definition of home-cooking, with older-generation, lower-educated, non-working and 'traditional' nuclear households being more likely to spend a larger share of their food budget on non-convenient and 'shortcut' ingredients.